Combined or Serial Liver and Lung Transplantation for Epithelioid Hemangioendothelioma: A Case Series. Issue 12 (19th August 2015) - Desie, N.; Van Raemdonck, D. E.; Ceulemans, L. J.; Nevens, F.; Verslype, C.; Vansteenbergen, W.; Pirenne, J.; Monbaliu, D.; Roskams, T.; Verbeken, E. K.; Neyrinck, A. P.; Dupont, L. J.; et al.
Abstract : Epithelioid hemangioendothelioma (EHE) is a rare vascular tumor with variable biological and clinical behavior. There is increasing experience with liver transplantation (LiTx) for hepatic EHE, even in cases of extrahepatic disease localization. Until now, no cases of lung transplantation (LuTx) had been reported for pulmonary EHE. This report describes three cases of EHE with multifocal disease in patients who underwent either serial or combined LiTx and LuTx. Abstract : This case series describes three patients with multifocal epithelioid hemangioendothelioma who underwent serial or combined liver and lung transplantation.